Augmenting visual design: Designing the changing classroom. (September 2020) - Sinfield, David; Cochrane, Thomas
Art and design undergraduate educational programmes such as Graphic Design studies are based upon best practice within the Graphic Design industry. Thus, the classroom environment is designed to mirror a typical design studio environment. However, traditional design studio interaction and collaboration are undergoing rapid transformation in practice triggered by an increasingly global digitally networked professional environment. In response, this paper outlines our journey of redesigning an undergraduate graphic design curriculum to enable students to engage beyond the context of the classroom to a potentially global audience. Over two redesign iterations Visual Communication Design students explored new technologies including mobile augmented reality and virtual reality to enhance the reach and impact of their portfolios of work. Using the concept of Visual Poetry and a combination of typography and moving image, the students created a range of art pieces inspired by a specific location, and shared these via an ecology of resources chosen to digitally augment their work and facilitate the production of student eportfolios. The goal of the curriculum redesign is to broaden students' educational experiences beyond the confines of the traditional studio based classroom to include wider community outreach and participation within an increasingly global environment.